Delivery of dexamethasone from bioactive nanofiber matrices stimulates odontogenesis of human dental pulp cells through integrin/BMP/mTOR signaling pathways - Lim HC (Dove Medical Press, 2016)
Hyun-Chang Lim,1,* Ok Hyung Nam,2,* Mi-joo Kim,3 Ahmed El-Fiqi,4,5 Hyung-Mun Yun,3 Yoo-Mi Lee,3 Guang-Zhen Jin,4,5 Hae-Hyoung Lee,5,6 Hae-Won Kim,4–6 Eun-Cheol Kim3 1Department of Periodontology, 2Department of Pediatric Dentistry, 3Department of Oral and Maxillofacial Pathology, Research Center for Tooth and Periodontal Regeneration (MRC), School of Dentistry, Kyung Hee University, Seoul, 4Department of Nanobiomedical Science, BK21 PLUS NBM Global Research Center for Regenerative Medicine, 5Institute of Tissue Regeneration Engineering, 6Department of Biomaterials Science, College of Dentistry, Dankook University, Cheonan, Republic of Korea *These authors contributed equally to this work as first authors Abstract: Therapeutically relevant design of scaffolds is of special importance in the repair and regeneration of tissues including dentin and pulp. Here we exploit nanofiber matrices that incorporate bioactive glass nanoparticles (BGNs) and deliver the odontogenic drug dexamethasone (DEX) to stimulate the odontogenic differentiation of human dental pulp cells (HDPCs). DEX molecules were first loaded onto the BGN, and then the DEX-BGN complex was incorporated within the biopolymer nanofiber matrix through electrospinning. The release of DEX continued over a month, showing a slow releasing profile. HDPCs cultured on the DEX-releasing BGN matrices were viable, proliferating well up to 14 days. The odontogenic differentiation, as assessed by alkaline phosphatase activity, mRNA expression of genes, and mineralization, was significantly stimulated on the matrices incorporating BGN and further on those releasing DEX. The DEX-releasing BGN matrices highly upregulated the expression of the integrin subsets α1, α5, and β3 as well as integrin downstream signaling molecules, including focal adhesion kinase (FAK), Paxillin, and RhoA, and activated bone morphogenetic protein mRNA and phosphorylation of Smad1/5/8. Furthermore, the DEX-releasing BGN-matrices stimulated Akt and mammalian target of rapamycin (mTOR), which was proven by the inhibition study. Collectively, the designed therapeutic nanofiber matrices that incorporate BGN and deliver DEX were demonstrated to promote odontogenesis of HDPCs, and the integrins, bone morphogenetic protein, and mTOR signaling pathways are proposed to be the possible molecular mechanisms. While further in vivo studies are still needed, the DEX-releasing bioactive scaffolds are considered as a potential therapeutic nanomatrix for regenerative endodontics and tissue engineering. Keywords: drug delivery, therapeutic matrix, dexamethasone, bioactive glass, human dental pulp cells, odontogenic differentiation